The Relationship between Motivation at Work and Organizational Commitment of the Arabic Translators in a Private Hospital in Bangkok - Khongwong, Sirirat; Sanamthong, Ekkasit; Koohathongsumrit, Nitidetch (Interdisciplinary Academic and Research Journal, 2023)
Human resources are considered the most important factor in achieving an organization’s goals, and corporate vision to build trust with Middle Eastern patients, the organization must provide knowledgeable staff. Proficiency in the Arabic language is critical to serving Middle Eastern patients, which creates competition among individual private hospitals in Bangkok. To increase the growth potential of individual hospitals in Bangkok, incentives must be provided to convince Arabic translators to stay with the organization for the long term. The purpose of this research is to study 1) the performance motivation of Arabic translators, 2) engagement with the organization, and 3) the relationship between motivation of performance with commitment to the organization of 131 Arabic translators in a private hospital in Bangkok. The research instruments were open-ended and closed-ended questionnaires. The statistics to analyze data namely frequency, percentage, mean, standard deviation, Pearson correlation, and stepwise multiple regression analysis for determining the effects of motivational factors on commitment to the organization. The research findings found that Arabic translators at a private hospital in Bangkok have both factors on achievement motivation: Motivation and Sustaining factors, which overall are at high levels and the level of opinions on organizational commitment is high overall. In the correlation analysis, it was found that the positive correlation between the performance motivation factor and organizational commitment is strong, with a statistical significance of 0.01, and the maintenance factor with a statistical significance of 0.05.